Temperature cycles beneath, and adjacent to, intertidal boulders and associated differences in biotic composition. Issue 4 (2nd October 2021) - van Rensburg, C; Robbins, A; Griffiths, C
Abstract : The only previous study on the macrobiota of South African boulder shores showed this assemblage to be more diverse than on nearby rocky platforms, but the drivers of that difference remain unresolved. We recorded water and air temperatures under intertidal boulders and on adjacent exposed rocky platforms, at both the upper- and lower-shore level, at Kommetjie, South Africa, over 2-week tidal cycles, repeating this during summer and winter. The macrobiota in each location was also sampled during diurnal low tides. The most-extreme temperatures, and greatest ranges, occurred during summer on upper-shore open rock (13.9–37.7 °C, range difference of 23.8 °C), while under upper-shore boulders the maximum temperature was lower at 28.9 °C and the range spanned only 15.5 °C. In winter, maximum temperatures and ranges were lower at all locations. Maximum temperatures did not coincide with spring tides, but occurred several days later, when low tides happened during the heat of the day. Closer analysis of daily fluctuations revealed influence of weather on temperatures attained and showed that durations of elevated temperatures were much shorter in the lower shore. The upper shore exhibited low biodiversity, supporting only 9 species, with 8 found only under boulders during diurnal low tide; the lower shore was more diverse, with 11 species on open rock and 29 under boulders. Biomass and abundance were also higher under boulders at both levels, especially on the upper shore. More-benign under-boulder conditions thus facilitate more abundant and diverse biota sheltering there than occurs on adjacent exposed rocks, particularly on the upper shore.